Personality traits and academic attitudes of medical students in the COVID-19 pandemic: a person-centered approach, empirical research, Korea - Jaesang Hwang; Ji Hye Yu; Janghoon Lee; Ikhan Kim; Su Jin Chae; Mijin Lee; Janghee Park (Korean Journal of Medical Education)
Purpose Since the coronavirus disease 2019 (COVID-19) pandemic, the educational environment has moved toward online-based education, which may significantly impact medical students’ educational experiences. However, the same events may be understood differently by different individuals depending on their personalities. Therefore, the changing educational environment during the COVID-19 pandemic may not have been perceived equally by all students. This study aimed to investigate medical students’ personality profiles and the difference between academic burnout and engagement according to their personality profiles. Methods During the 2021–2022 academic year, when online-based education was implemented due to the pandemic, a survey was conducted among medical students in Korea (N=325). First, we used latent profile analysis to identify the sub-types of the Big Five personalities. Second, we used analysis of variance and post hoc comparisons to study the difference between academic burnout and engagement among these sub-types. Results The Big Five personality traits of medical students in our sample were classified into three profiles. Profiles with relatively high neuroticism, while other personality traits were low, had both the highest academic burnout and academic engagement. Alternatively, the profiles showing relatively low neuroticism, while other personality traits were high, had the lowest academic burnout and the highest academic engagement. Conclusion Personality is a stable trait that affects an individual’s behavior and response to the environment. Thus, individuals with specific personalities differ in their reactions to their environment. This may provide an advantage to some medical students’ careers.